Quality of Life in Jewish Bioethics - Zohar, Noam J. (Lexington Books, 2006)
This anthology of original essays by leading thinkers in the field gathers together in one place voices from diverse theological and practical commitments. Unlike other publications on Jewish bioethics, it adopts an explicitly pluralistic stance. The book addresses tension between the 'quality of life' and the 'sanctity of life' issues, and will be of interest to lay readers, graduate students of bioethics, and rabbis.